Judyta Zamrzycka, Toruń’s bookbinders from the 15th to the16th/17th centuries – the typology of technical features of the trade - Kopiński, Krzysztof (Folia Toruniensia, 2017)
The text discusses and reviews the work by Judyta Zamrzycka titled Introligatorzy toruńscy od XV do XVI/XVII wieku – typologia cech warsztatowych, which was published in 2014. The construction of the work is quite interesting. One-third of the content of the book constitutes the documentation base, which is the result of the query. The remaining two-thirds of the publication include the theoretical part and the overview of the findings. Judyta Zamrzycka examined incunables and prints from the collections of the Copernicus Regional Public and Municipal Library in Toruń (altogether 148 volumes) and manuscripts from the State Archive in Toruń (in total 8 volumes). The book by Judyta Zamrzycka deserves to be praised owing to the comparative method of the analysis of the covers of manuscripts and incunables and the research on bookbinding workshops in the Polish territories.